Stable Covalent pH-Sensitive Metallophthalocyanines Thin Monolayer Films for Selective Detection of Neurotransmitters - Idowu, Abosede Omowumi Atinuke (Rhodes University, Faculty of Science, Department of Chemistry)
The global challenge in solving the problem of neurodegenerative diseases (NDDs) that affect neurons in the human brain is to date unresolved. The statistical population of the affected people increases each year. Neurons are prone to damage or death as a result of an imbalanced level of released neurotransmitters (NTs). These imbalances affect the proper functioning of the brain and body. Early detection of the imbalances of NTs could suppress or correct the symptoms of NDDs. The detection has been the focus of researchers employing different techniques for both in-vivo and in-vitro detection of NTs. The research is based on electrochemical technique due to its fast response with adequate qualitative and quantitative results. The electrochemical methods are easy to handle, and the working electrode in the system can be modified for a specific purpose. The materials used in this work were the first-row transition metals octacarboxyphenoxy phthalocyanines complexes. The complexes were immobilized onto gold electrode surfaces and used as electrocatalysts for the detection of NTs. The immobilization method used to modify gold electrode was highly stable throughout the analyses in this study. The complexes improved the efficiency of the gold electrodes towards the detection of the NTs and suppressed the presence of ascorbic acid as a strong interference. The focus of this research is to solve the problem of interference faced during the detection of NTs. The thin film of octacarboxyphenoxy metallophthalocyanines was immobilized onto the gold electrode. The complexes, due to their catalytic activity, detected dopamine, epinephrine, serotonin and norepinephrine accurately. The range of detection of prominent chemicals associated with NTs was done using electroanalytical methods. Due to the pH sensitive functional groups (COOH), the thin monolayer phthalocyanine films suppressed ascorbic acid interference. The electrochemical analysis of neurotransmitters gave excellent limit of detection at Î¼M range for all studied NTs. The results obtained with the modified electrode are proof of good electrocatalytic abilities of the complexes synthesized. This study recommends the use of the methods in this work for development of electrodes for NTs detection in human serum and tissue samples.
Keywords: Neurotransmitters; Phthalocyanines; Monomolecular films; Nervous system Degeneration